Characterization of Circulating Androgens, Cortisol and Estrogens During Normal, Abnormal and False Pregnancy in Bottlenose Dolphins (Tursiops truncatus) Under Managed Care - Steinman, K. J.; Montano, G. A.; Robeck, T. R. (Frontiers in Marine Science, 2021)
The few hormone studies on bottlenose dolphin (Tursiops truncatus) pregnancy with different reproductive outcomes, e.g., normal birth, stillbirth and abortion, have mostly focused on progestagens or relaxin. However, recent analysis of androgens, glucocorticoids and estrogens has shown they are also biomarkers of cetacean pregnancy. Therefore, our objective was to examine circulating concentrations of androgens, glucocorticoids and estrogens during bottlenose dolphin pregnancies with different reproductive outcomes, including normal pregnancy (NORM, n = 27), failure to thrive (FTT, n = 17), perinatal loss (PNL, n = 20), early loss (EL, n = 12) and false pregnancy (FP, n = 16), to determine if they could be potential indicators of reproductive or fetal health. We analyzed longitudinal serum samples (n = 654) from 57 bottlenose dolphins and 92 reproductive events for testosterone, androstenedione, cortisol, estradiol and estrone conjugates. Testosterone concentrations were higher during EL compared to NORM and lower during FP during MID (day 121– 240 post ovulation/conception) and LATE (day 241 – end of FP) stages (months post conception/ovulation [MPC, MPO] seven through ten, P < 0.05). During FTT, androstenedione concentrations were increased compared to NORM pregnancies in the EARLY and LATE stages (P ≤ 0.05), and concentrations were reduced during FP (P < 0.05). For cortisol, FTT pregnancies had higher concentrations compared to NORM during all stages (P < 0.05), while PNL had higher cortisol during EARLY and LATE stages (P < 0.05). Estradiol concentrations were lower for EL and FP compared to NORM (P < 0.05), while estrone conjugates were only reduced during FP (P < 0.05). Based on our results only cortisol may be a useful predictor of PNL, while both cortisol and androstenedione were useful for distinguishing FTT pregnancies. Similarly, both testosterone and estradiol during EL and FP were different from NORM. Our data indicate a suite of pregnancy specific hormone biomarkers to evaluate maternal and fetal health in bottlenose dolphins should include cortisol, androgens and estrogens. This research also highlights the importance on non-progestagen hormones as sentinels of cetacean pregnancy and fetal health.